Rockets and feathers: Asymmetric pricing and consumer search - Evidence from electricity retailing - Sven Heim (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2019)
In many markets prices react stronger to rising than to falling costs. This asymmetric cost pass-through is still not fully understood, but recent theories suggest that asymmetric adjustments of consumers' search efforts to rising and to falling prices may help to explain this. I use novel panel data to investigate the interaction of consumer search intensity, pricing and cost pass-through in the German residential electricity markets. I find that consumers search slightly more when prices rise but drastically decrease search efforts when they fall. Moreover, I find direct evidence that cost pass-through heavily depends on consumers' search efforts.
Keywords: D83; L11; 330; Consumer Search; Cost Pass-through; Rockets and Feathers